Percutaneous Management of Bioprosthetic Mitral Valve Dehiscence with Combined Valve-in-Valve Replacement and Paravalvular Leak Closure - Hani Alturkmani; Jack Xu; Adib Chaus; Srikanth Vallurupalli; Gaurav Dhar (Methodist DeBakey Cardiovascular Journal)
This case report describes a patient with bioprosthetic mitral valve dehiscence that resulted in severe paravalvular regurgitation and cardiogenic shock. Due to prohibitive surgical risk, valve-in-valve transcatheter mitral valve replacement was attempted but did not reduce the severity of the prosthetic paravalvular leak (PVL) severity. Subsequent percutaneous PVL closure with a ventricular septal defect occluder successfully reduced the PVL severity and led to significant clinical improvement.